Cluster analysis identifies three clinical patterns of patients with systemic autoimmune diseases and anti-Ku antibodies - Bruno Fautrel; Zahir Amoura; Yves Allenbach; Olivier Benveniste; Samuel Bitoun; Xavier Mariette; Luc Mouthon; Benjamin Terrier; Philippe Dieude; François Chasset; Brigitte Bader-Meunier; Raphaele Seror; et al. (RMD Open)
Objective To determine distinct patterns of patients with autoimmune diseases harbouring anti-Ku antibodies and their respective prognosis.Methods Anti-Ku-positive patients were retrieved through four immunology departments. Clusters were derived from unsupervised multiple correspondence analysis, not including the disease’s diagnosis, followed by hierarchical clustering. Baseline characteristics and risk of disease progression, defined as a composite of new organ involvement or the need for new immunosuppressants, were compared across the retrieved clusters.Results Among 154 anti-Ku-positive patients, three clusters were identified. At disease’s onset, all patients included in cluster 1 (n=42/154, 27%) had muscle involvement, 34% displayed cardiac manifestations. Inflammatory myopathies (n=35/42, 83%) and/or systemic sclerosis (n=17/42, 40%) were the most frequent diagnoses. Cluster 2 (n=69/154, 45%) included the lowest proportion of women (68% vs 83% and 84% in clusters 1 and 3), 54% of patients had lung involvement, and 25% fulfilled Sjögren’s disease criteria. Cluster 3 (n=43/154, 28%) included younger patients (median age 25 years), with 79% of them fulfilling systemic lupus erythematosus criteria. These three clusters have distinct outcomes (p=0.001): cluster 1 developed lung involvement and displayed the higher risk of disease progression, cluster 2 was prone to myositis development and cluster 3 developed various clinical manifestations. The proportion of patients with heart involvement doubled over time in all clusters, with a majority of myocarditis in cluster 1, pulmonary hypertension in cluster 2 and pericarditis in cluster 3.Conclusion Three distinct groups of anti-Ku-positive patients were identified; cardiac involvement should be carefully tracked throughout the follow-up in all of them.